Guftimān-i zanāna - Sirāǧ, ʿAlī (Intišārāt-i Rawšangarān wa Muṭālaʿāt-i Zanān, 2016)
Women authors, Iranian ; Persian literature - Women authors - History and criticism
Keywords: Women authors; Iranian; Persian literature / Women authors / History and criticism; Persisch; Frauenliteratur